(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This thesis examines the genre and polemical specificity of publicistic writings in the English Enlightenment and Central Asian Jadid literature. The analysis focuses on Daniel Defoe, Jonathan Swift, Alexander Pope, Joseph Addison, Richard Steele, Mahmudkhoja Behbudiy, Abdurauf Fitrat, Abdulla Avloniy and Abdulhamid Chulpan. Although these writers belonged to different historical and cultural contexts, their works reveal a common reformist orientation. In both traditions, polemics functioned as a means of social criticism, moral education and intellectual renewal. English Enlightenment polemics was mainly expressed through the essay, pamphlet, periodical article, satire and poetic criticism. Jadid polemics developed through journalistic articles, dramatic dialogue, educational treatises, public appeals and reformist essays. The comparison shows that both traditions were united by the idea of enlightenment, but differed in genre form, social urgency and historical function.